The Immediate Effects of a Single 20-Minute Session of Transcranial Direct Current Stimulation (tDCS) on Muscle Strength in Older Adults - Adchaithor, Piangdaw; Auvichayapat, Paradee; Punjaruk, Wiyada; Tunkamnerdthai, Orathai (Trends in Sciences, 2024)
The older population often experiences a gradual age-related decline in the primary motor cortex, leading to muscle weakness that can harm their physical performances. Exercise could improve physical performance and prevent falling in older adults. However, the decrease in motor function and motor skills in older adults reduces the efficiency of fall prevention. Transcranial Direct Current Stimulation (tDCS) is a non-invasive intervention aimed at improving muscle strength in various conditions by utilizing transcranial direct current stimulation applied to the primary motor cortex (M1). Pre- and post-studies were conducted to demonstrate the effects of a single 20-minute session of tDCS alone, as well as to assess any potential side effects. Sixteen older individuals, both male and female, aged 65 years or older, with or without underlying diseases, were assessed for leg and hand grip strength, followed by physical performance tests. Subsequently, they underwent stimulation of the primary motor cortex through the placement of anodal tDCS (a-tDCS) over the left M1 for 20 min. Immediate effects were evaluated within 24 h, and side effects were recorded for up to 2 weeks after the stimulation. The results demonstrated that a single session of tDCS led to a significant increase in leg strength by 13 kg (5.9 to 20.1 kg, p < 0.01). There was also a significant correlation observed with hand grip strength (r = 0.68, p < 0.01). All physical performance tests, except the fastest speed in the 10-meter walk test, showed statistically significant improvements (p < 0.01). Participants reported no serious side effects, and the intervention will now be incorporated into prospective clinical studies involving older populations to compare its effectiveness with other treatments. HIGHLIGHTS A single session of tDCS led to a significant increase in leg strength. A single session of tDCS, with a significant correlation observed with hand grip strength. Physical performance tests showed statistically significant improvements after a single session of tDCS. Participants reported no serious side effects. This intervention will now be incorporated into prospective clinical studies involving older populations to compare its effectiveness with other treatments. GRAPHICAL ABSTRACT